Sofosbuvir as a potential option for the treatment of COVID-19 - Nourian, Anahid; Khalili, Hossein (Acta Biomedica Atenei Parmensis, 2020)
Sofosbuvir may be a potential option in the treatment of COVID-19 based on the similarity between the replication mechanisms of the HCV and the coronavirus. According the limited experimental evidences, it is hypothesized that sofosbuvir might be a potential option to improve care of patients with COVID-19 especially at the start of the disease and before invasion of the virus into the lung parenchymal cells. Efficacy and safety of sofosbuvir in treatment of COVID-19 may be considered in future clinical studies.